Fabrication Of 3d Double-network Cnc/alg/pegda Printed Constructs Seeded With C2c12 Myoblasts For Bioprinting Applications - Asohan, Anusha Wei (2023)
3D bioprinting offers a promising alternative for articular cartilage repair and regeneration using a layer-by-layer predetermined movement from a computer aided (CAD) software. In this project, a bioink for bioprinting applications was formulated using cellulose nanocrystals (CNCs), alginate (Alg), and poly(ethylene glycol) diacrylate (PEGDA). Firstly, different formulations of CNC/Alg/PEGDA were formulated using a double network crosslinking approach where the hydrogel was first ionically crosslinked with Ca2+ ions and subsequently photo-crosslinked under UV irradiation at 365nm post-extrusion. The rheological properties, swelling behaviour, and mechanical properties of the formulations were assessed to determine the optimal formulation for bioprinting. Then, the printability of the selected CNC/Alg/PEGDA formulation was evaluated using an extrusion based bioprinter. Next, the biocompatibility of the selected CNC/Alg/PEGDA formulation was determined using C2C12 myoblasts. The cells were seeded into the hydrogel, followed by the bioprinting process. The viability of cells was assessed using Live/Dead assay for a period of 14 to 16 days. The internal structure and porosity of the bioprinted construct with and without cells was analysed using scanning electron microscopy (SEM). Based on the preliminary results, Formulation 8 (F8) with the concentration of 4% CNC, 4% Alg and 40% PEGDA demonstrated shear-thinning behaviour with power-law inde